Strontium substituted hydroxyapatites: Synthesis and determination of their structural properties, in vitro and in vivo performance - Kaygili, Omer; Keser, Serhat; Kom, Mustafa; Eroksuz, Yesari; Dorozhkin, Sergey V.; Ates, Tankut; Yakuphanoğlu, Fahrettin (Elsevier, 2015)
The objective of this study is to present a detailed report related to the synthesis and characterization of strontium substituted hydroxyapatites. Based on this purpose, hydroxyapatite (HAp) bioceramics with different amounts of strontium (e.g., 0, 0.45, 0.90, 135, 1.80 and 2.25 at.%) were prepared using a sol-gel method. The effects of Sr substitution on the structural properties and biocompatibility of the samples were studied by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) techniques, in vitro and in vivo tests. All the samples composed of the nanoparticles ranging from 21 to 27 nm. The presence of Sr at low levels influenced the crystal size, crystallinity degree, lattice parameters and volume of the unit cell of the HAp. Both in vitro conditions and soaking period in simulated body fluid (SBF) significantly affected these properties. Especially, the (Ca + Sr)/P molar ratio gradually decreases with increasing soaking period in SBF. Animal experiments revealed the bone formation and osseointegration for all samples, and as compared with other groups, more reasonable, were observed for the sample with the lowest Sr content. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; In vitro; In vivo; Strontium